If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + 8x = (7 + -1x) Remove parenthesis around (7 + -1x) 37 + 8x = 7 + -1x Solving 37 + 8x = 7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 37 + 8x + x = 7 + -1x + x Combine like terms: 8x + x = 9x 37 + 9x = 7 + -1x + x Combine like terms: -1x + x = 0 37 + 9x = 7 + 0 37 + 9x = 7 Add '-37' to each side of the equation. 37 + -37 + 9x = 7 + -37 Combine like terms: 37 + -37 = 0 0 + 9x = 7 + -37 9x = 7 + -37 Combine like terms: 7 + -37 = -30 9x = -30 Divide each side by '9'. x = -3.333333333 Simplifying x = -3.333333333
| X=(13/5)*y | | X=(13/5)×y | | 14=.5(8x+12) | | X=(13/5)y | | 14=.5 | | (6y-5x)(3y-7x+4)= | | 3/4g=28 | | 6x+16=3x+17 | | 3h-6+2h=-2+h | | X^2-2ax-1=0 | | 5(2-x)-3(4-2r)=20 | | 2b+3=b+19 | | 15x^3+3x= | | 3l-6+2l=-2+l | | 6i/5+3i= | | [2x-2]=6 | | 5y=7x+2 | | 189=9-9x | | -(0.79k+0.227)=-(2.09k+0.838) | | 6/4+6i= | | p^3(e^5p-7)-(6p/2_p^2) | | lnx+2=7+lnx-1 | | lnx^3=7lnx | | 5/7×3/4=? | | 4i/8+2i= | | -2x+2=5y | | (2x-1/3)^2 | | 1/3(9h*h-6h) | | 9x/2-10x=7 | | 3(2x+1)+4=24 | | 7x^2-48x+7=0 | | 1/2-1/8=? |